Stereotypes and education level: An influence on the selection of engineering studies and techno-scientific education - Mejía, Camila; Pabón, Milton; Pupiales, Jayro; Chiluisa, Katheryne; Ramírez Paredes, Fernando (EASI: Engineering and Applied Sciences in Industry, 2023)
This work addresses the possible causes why students do not opt for an engineering career or techno-scientific education, facts evidenced through obtaining a sample of the engineering faculties at the Universidad Técnica del Norte, the possible causes of this statistic were revealed. The surveys were successfully carried out with the collaboration of the authorities and the students. The analysis of results reveals that gender stereotypes are still present in society, affecting students when selecting a career. The history of engineering goes back to the great ancient civilizations, but the participation of women in engineering is partially recent. It is necessary to recall that engineering branches and techno-scientific education were reserved for men for a long time, since education in general was far from the reach of women.